Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Number: 2
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

The physical burden of water carrying and women’s psychosocial well-being: Evidence from rural nepal - Tomberge, Vica Marie J.; Bischof, Janine Stefanie; Meierhofer, Regula; Shrestha, Akina; Inauen, Jennifer (International Journal of Environmental Research and Public Health, 2021)
Dans les pays à faible revenu, de nombreuses femmes transportent de lourdes charges d'eau potable pour leur famille sur des terrains difficiles. Cela peut nuire à leur santé et à leur bien-être. La présente étude est la première à examiner la charge physique du transport de l'eau et le bien-être psychosocial des femmes, ainsi que la manière dont cette relation est modérée par les conditions environnementales et sanitaires. Des enquêteurs locaux formés ont mené des entretiens avec 1 001 femmes dans cinq communautés rurales du Népal. En outre, des mesures objectives ont été utilisées pour évaluer le poids porté et la distance par rapport à la source d'eau. La charge physique du transport de l'eau a été calculée à partir du poids, de la distance et de la fréquence des déplacements. Son association avec le bien-être psychosocial a été modélisée à l'aide d'équations d'estimation généralisées. Deux autres modèles incluaient le terrain et le prolapsus utérin comme modérateurs. La charge physique du transport de l'eau est directement liée à une détresse émotionnelle plus élevée et à une réduction du fonctionnement quotidien. Cette corrélation était exacerbée pour les femmes transportant sur un terrain vallonné par rapport à un terrain plat, et pour celles qui souffraient d'un prolapsus utérin. Nos résultats soulignent l'importance d'un accès adéquat à l'eau pour le bien-être psychosocial des femmes, en particulier pour les populations vulnérables telles que les femmes en mauvaise santé (par exemple, prolapsus utérin) ou celles vivant dans des terrains vallonnés. Les résultats soulignent en outre l'interdépendance de l'Objectif de développement durable (ODD) 6 : accès à l'eau, de l'ODD 3 : santé et bien-être et de l'ODD 5 : égalité des sexes.
Keywords: 2000 à aujourd'hui; asie; bien-être psychosocial; environnement; histoire et politique; népal; projet charge mentale; périodes historiques; régions géographiques; santé; santé des femmes*; thématiques; transport de l'eau potable; travail; travail reproductif

Its about time we care about an equitable world: Women's unpaid care work and COVID-19 - Sarrasanti Ardinugroho, Nediana; Donkor, Felix Kwabena; Santos, Claudia; Tsagkari, Marula; Wannous, Chadia (IEEE Engineering Management Review, 2020)
Unpaid care work, mostly performed by women, is a central but undervalued contributor to economies. During the COVID-19 pandemic, the need for unpaid care work increased due to restricted movement, social isolation, and economic challenges. This pandemic has highlighted the urgency of recognizing and valuing women's work at the household level which has been systematically overlooked. At the same time, it has increased the demand for technology usage, exposing the gender digital divide. This article aims to shed light on the additional burden women are facing, especially when trying to balance unpaid care work with paid employment from the seclusion of their homes. We do this by reviewing a number of surveys conducted in Indonesia. We combine this with other examples from additional contexts in order to draw attention to a global trend of amplified inequalities and struggles women are experiencing. We advocate for an urgent paradigm shift by providing vital recommendations for policymakers and managers.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; covid-19; indonésie; pandémie; pauvreté; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail non rémunéré; travail précaire; violences; violences domestiques; violences envers les femmes*

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Number: 5 Place: Birmingham Publisher: Emerald Group Publishing Limited
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

Santé sexuelle et autonomie reproductive : étude qualitative sur les expériences et représentations des femmes universitaires de Mumbai, Inde - Beauchemin-Roy, Sarah (Université du Québec à Montréal, 2018)
Cette recherche vise à explorer les expériences et représentations des femmes indiennes universitaires quant à leur santé sexuelle et reproductive. Plus précisément, il s'agit d'explorer les normes sociales et les enjeux associés à la décision d'avoir une vie sexuelle active ; de documenter les expériences et perceptions des femmes quant à leurs connaissances et à l'utilisation des méthodes de contraception ; et de décrire leur pouvoir de décision et de contrôle sur leur stratégie contraceptive. Pour y arriver, une recherche qualitative exploratoire a été menée de septembre à novembre 2016 à Mumbai, en Inde. Les 10 participantes sont des étudiantes au collège ou à l'université, sexuellement actives dans les douze derniers mois, âgées de 20 à 25 ans, qui ont pris part à une entrevue semi-dirigée de 60 minutes. Les résultats indiquent que les jeunes femmes universitaires font face à de nombreux obstacles à l'atteinte d'une autonomie reproductive et donc, d'une santé sexuelle et reproductive optimale. Tout d'abord, les normes patriarcales établies par les structures sociales et culturelles influencent les représentations de la sexualité féminine dans la société. Ensuite, quant aux expériences sexuelles des participantes, elles sont modulées par la famille et le réseau des pairs ; le premier étant un obstacle et le deuxième étant un facilitateur à la transgression des normes et des attentes sociales envers les femmes. Enfin, plusieurs facteurs interpersonnels et individuels élaborés dans ce mémoire jouent un rôle déterminant dans l'atteinte d'une autonomie reproductive. Pour conclure, il sera pertinent de se pencher sur les limites de cette recherche ainsi que sur des recommandations. Or, considérant que des changements majeurs sont nécessaires à plusieurs niveaux, des recommandations globales seront proposées. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : autonomie reproductive, santé sexuelle et reproductive, justice reproductive, méthodes contraceptives, étudiantes collégiales et universitaires, Mumbai, Inde
Keywords: 2000 à aujourd'hui; 2010-2019; IREF; asie; contraception; discipline; inde; justice reproductive; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; étudiantes indiennes

The association between satisfaction with husband's participation in housework and suicidal ideation among married working women in Korea. - Lee, Sang Ah; Park, Eun-Cheol; Ju, Yeong Jun; Han, Kyu-Tae; Yoon, Hyo Jung; Kim, Tae Hyun (Psychiatry research, 2018)
Although married women are increasingly participating in paid labor, housework remains their primary responsibility. This uneven distribution of housework could have a negative impact on their mental health. In this study, we examined the association between satisfaction with husbands' participation in housework and suicidal ideation in married working women. Data were obtained from 3544 participants of the fourth and fifth waves of the Korean Longitudinal Survey of Women and Families. Satisfaction with husbands' participation in housework was classified as satisfactory, less satisfactory, and dissatisfactory. A generalized estimating equations model was used to examine the association. Those who were dissatisfied with their husbands' participation in housework were 2.65 times more likely to think about suicide than those who were satisfied. Subgroup analysis showed that women with an egalitarian gender ideology or low job dissatisfaction were more likely to think about suicide when they were dissatisfied with their husbands' participation in housework. In conclusion, married working women who were dissatisfied with their husbands' participation in housework are more likely to think about suicide than those who are satisfied. Therefore, fostering an environment of fair distribution of housework is necessary for alleviating their stress from the dual burden of work and family. (Copyright © 2018 Elsevier B.V. All rights reserved.)
Keywords: 2000 à aujourd'hui; 2010-2019; asie; charge mentale; corée du sud; discipline; maternité; médecine; projet charge mentale; psychiatrie; périodes historiques; régions géographiques; santé; santé mentale des femmes mariées; suicide; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

Voices of South Asian Women: Immigration and Mental Health - Ahmad, Farah; Shik, Angela; Vanza, Reena; Cheung, Angela M.; George, Usha; Stewart, Donna E. (Women & Health, 2005)
Purpose: This qualitative research aimed to elicit experiences and beliefs of recent South Asian immigrant women about their major health concerns after immigration. Methods: Four focus groups were conducted with 24 Hindi-speaking women who had lived less than five years in Canada. The audiotaped data were transcribed, translated, and analyzed by identification of themes and subcategories. Results: Mental health (MH) emerged as an overarching health concern with three major themes, i.e., appraisal of the mental burden (extent and general susceptibility), stress-inducing factors, and coping strategies. Many participants agreed that MH did not become a concern to them until after immigration. Women discussed their compromised MH using verbal and symptomatic expressions. The stress-inducing factors identified by participants included loss of social support, economic uncertainties, downward social mobility, mechanistic lifestyle, barriers in accessing health services, and climatic and food changes. Women's major coping strategies included increased efforts to socialize, use of preventative health practices and self-awareness. Conclusion: Although participant women discussed a number of ways to deal with post-immigration stressors, the women's perceived compromised mental health reflects the inadequacy of their coping strategies and the available resources. Despite access to healthcare providers, women failed to identify healthcare encounters as opportunities to seek help and discuss their mental health concerns. Health and social care programs need to actively address the compromised mental health perceived by the studied group.
Keywords: amériques; asie; asie du sud; canada; charge mentale; cours; discipline; femmes immigrantes; médecine; régions géographiques; santé; sciences; soc1061; stress post immigration; thématiques

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

Contraception masculine et querelles de genre - Oudshoorn, Nelly; Akrich, Madeleine; Le Doaré, Hélène (Cahiers du Genre, 1999)
Depuis la seconde guerre mondiale, treize nouveaux contraceptifs féminins ont été émis au point alors que les contraceptifs masculins sont à peu près inchangés depuis quatre cents ans. La responsabilité contraceptive, avec les risques qui en découlent pour la santé, est donc attribuée principalement aux femmes. Cet article se propose d’analyser le rôle de différents acteurs dans la réécriture éventuelle des rapports de genre autour de la contraception. Nous nous concentrerons sur le cas des nouvelles techniques contraceptives, surtout masculines, et la manière dont leurs utilisateurs sont définis. Alors que la plupart des travaux en sociologie des techniques insistent sur le rôle de l’innovation dans cette définition de l’utilisateur, nous montrerons qu’aux côtés des scientifiques, les féministes et les journalistes ont joué un rôle important dans la configuration des utilisateurs potentiels de ces techniques contraceptives : ils ont construit une grande variété de représentations de la masculinité et des utilisateurs hommes. Ces représentations sont utilisées soit pour montrer qu’il n’y a pas d’obstacle culturel à l’acceptabilité de ces techniques, soit à l’inverse, pour en dénoncer le caractère utopique.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; asie; cours; discipline; discours dominant; europe; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques